Promoting Safe Winter Sports and Support for the Beijing 2022 Olympic and Paralympic Winter Games:A Global Collaborative Education Program - Guan Hongwe (Contemporary Social Sciences, 2018)
Safety is critically important for any sport or recreational activity. Skiing and snowboarding are winter activities that are potentially beneficial to health and fitness. However, they present a significant risk of injury. If not well managed, high injury rates will negatively impact the ski industry and its development. The purpose of this study was to systematically review the literature of safety and injury prevention programs specific to recreational alpine skiers and snowboarders in China and compare them with those implemented in the United States to promote safe snow sports and prepare skilled ski patrol and injury prevention professionals for the Beijing 2022 Olympic and Paralympic Winter Games.